Increased ionization supports growth of aerosols into cloud condensation nuclei - H. Svensmark (Nature Portfolio, 2017)
Ions produced by cosmic rays have been thought to influence aerosol and cloud processes by an unknown mechanism. Here the authors show that the mass flux of ions to aerosols enhances their growth significantly, with implications for the formation of cloud condensation nuclei.